Investigation into the effectiveness of electropalatography in treating persisting speech sound disorders in adolescents with co-occurring developmental language disorder. (4th March 2022) - Leniston, Hannah; Ebbels, Susan
ABSTRACT: This study aimed to assess the effectiveness of electropalatography (EPG) intervention in targeting specific phonemes/words in seven adolescents aged 14:10–18:06 with co-occurring speech sound and language disorders. Progress on individualised targets versus controls was evaluated following intervention undertaken as part of the participants' usual speech and language therapy provision. As a group, the participants showed significantly greater progress on their targets than controls, indicating that the EPG intervention was effective. However, performance varied between participants, targets and school terms. Factors that may have influenced the effectiveness of intervention include spending more time on targets and focusing on a specific phoneme. Overall, the results suggest EPG should be considered as an intervention approach for this client group, even in the late teenage years.